The Implementation Of Rewards And Punishments Towards Students Motivation In English Learning - L, Syahrir; hermansyah, Sam; Nadirah, Nadirah; Rasyid, Rustam efendy; Buhari, Buhari; Sartika, Sartika (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2023)
This research uses descriptive qualitative research as a research methodology located at SMP Negeri 3 Pitu Riase. This research was conducted to determine the implementation process of giving rewards and punishments to increase students' learning motivation and to find out the results of the implementation of giving rewards and encouragement to increase students' learning motivation in English subjects. Data collection techniques used are observation, interviews and documentation. While data analysis used data reduction, data presentation and data verification. The data obtained from this study is divided into two, namely data in the form of verbal (words) for example